High-speed density measurement for LNG and other cryogenic fluids using electrical capacitance tomography. (January 2021) - Hunt, Andrew; Rusli, Ijhar; Schakel, Menne; Kenbar, Asaad
Highlights: Review of density measurement methods for liquified natural gas. Design of a sensor based on electrical capacitance tomography for use in cryogenic flows. Testing of sensor design and materials in liquid nitrogen. Proposals for use of ECT sensor in LNG flows. Abstract: The global custody transfer market for liquefied natural gas (LNG) has grown at a strong pace in the last decade and use of LNG as transport fuel has considerable environmental benefits. The quantity of LNG is traded on the basis of energy transferred, calculated from volume, density and gross calorific value. High-speed, accurate density measurement is therefore of significant commercial value. The electrical capacitance tomography (ECT) device described in this paper has the potential to measure the LNG density rapidly, on-line at a moderate cost. Continuous monitoring of variation in LNG density during dynamic LNG flow measurement also gives a good indication of change in fluid quality and thus onset of boiling which is known to affect measurement accuracy. ECT is a leading candidate to be explored for online density measurements through measurement of electrical permittivity, as in addition to average value, it offers the image of permittivity across the whole flow conduit, allowing localised bubbles, boiling or other variations to be identified and measured. We report here experiments to explore the use of ECT in cryogenic applications. An 8-electrode test ECT sensor was designed, built and tested in laboratory conditions and then in liquid nitrogen. The resolution and imaging capability in cryogenic conditions are shown to be comparable to that under laboratory conditions. The experiments reported here use liquid nitrogen as an analogue fluid, but the results presented are believed to be representative of many cryogenic fluids. Although the use of ECT has been widely reported in the literature for multiphase flows in general, its use has not previously been reported for cryogenic flows. This paper offers proof of principle for ECT cryogenic multi-phase density and flow measurement. Dielectric constant is strongly linked to fluid density, and the ECT sensor design tested here shows an estimated measurement of the relative permittivity of liquid nitrogen of 1.45 with a standard measurement error of 0.034. Measurement stability at cryogenic conditions gave an rms variation of output under static conditions of better than 0.001 relative permittivity units even though it was unguarded and only a single electrode ring. The primary errors are associated with the unguarded nature of the test sensor, which was primarily designed as a proof of concept and material demonstrator. In addition, such an ECT sensor would provide clear images of any gas in the liquid and give a good estimation of the concentration and velocity of the gas bubbles. The scope of this work is to provide a proof of concept of the cryogenic ECT sensor.